THE USE OF MAKE A MATCH COOPERATIVE MODEL BY GRAPHICS MEDIA IN IMPROVING SOCIAL SCIENCE LEARNING AT THE FIFTH GRADE STUDENTS OF SDN MUNGGU IN THE ACADEMIC YEAR OF 2014/2015 - Sukmawati, Lilis (KALAM CENDEKIA PGSD KEBUMEN, 2015)
Abstract : The Use of Make a Match Cooperative Model by Graphics Media in Improving Social Science Learning at the Fifth Grade Students of SDN Munggu in the Academic Year of 2014/2015. The aims of this research is to improve Social Science learning at the fifth grade students. Subjects of this research were students in the fifth grade of SDN Munggu, consisting of 29 students. Classroom Action Research was conducted in three cycles. Each cycle consists of planning, action, observation, and reflection. The technique of collecting data were through observation, interviews, and test. The validity of data used triangulation of techniques and sources. Analysis of data applied through quantitative and qualitative analysis. Quantitative data analysis includes data reduction, data presentation, and conclusion. The result of this research is the use of Make a Match cooperative model by graphics media can improve Social Science learning. Keywords: Make a Match, graphics media, Social Science learning Abstrak : Penggunaan Model Kooperatif Make a Match dengan Media Grafis dalam Peningkatan Pembelajaran IPS pada Siswa Kelas V SDN Munggu tahun ajarann 2014/2015. Tujuan penelitian ini untuk meningkatkan pembelajaran IPS pada siswa kelas V. Subjek penelitiannya adalah siswa kelas V SDN Munggu sejumlah 29 siswa. Penelitian Tindakan Kelas ini dilaksanakan dalam tiga siklus. Setiap siklus terdiri dari perencanaan, pelaksanaan tindakan, pengamatan, dan refleksi. Teknik pengumpulan data dengan observasi, wawancara dan tes. Validitas data menggunakan triangulasi teknik dan sumber. Analisis data melalui analisis kuantitatif dan kualitatif. Analisis data kualitatif meliputi reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan penggunaan model kooperatif Make a Match dengan media grafis dapat meningkatkan pembelajaran IPS. Kata Kunci: Make a Match, grafis, pembelajaran IPS